2017
DOI: 10.1039/c6ob02278b
|View full text |Cite
|
Sign up to set email alerts
|

Boronic esters as protective groups in carbohydrate chemistry: processes for acylation, silylation and alkylation of glycoside-derived boronates

Abstract: Procedures for selective installation of acyl, silyl ether and para-methoxybenzyl (PMB) ether groups to glycoside substrates have been developed, employing phenylboronic esters as protected intermediates. The sequence of boronic ester formation, functionalization and deprotection can be accomplished with only a single purification step, and the boronic acid component can be recovered and reused after deprotection. Key advances include the identification of reaction conditions for installation of PMB groups in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 41 publications
1
46
0
Order By: Relevance
“…5,6 Transient protection via tricoordinate boronic ester formation has been used to accomplish selective acylations, glycosylations, sulfations, alkylations and silylations of carbohydrate derivatives. [7][8][9][10][11][12][13][14][15] polymer-supported boronic acids have also been developed. [16][17][18] A complementary and less widely exploited mode of reactivity for organoboron complexes of sugars is the activation of OH groups by formation of tetracoordinate adducts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Transient protection via tricoordinate boronic ester formation has been used to accomplish selective acylations, glycosylations, sulfations, alkylations and silylations of carbohydrate derivatives. [7][8][9][10][11][12][13][14][15] polymer-supported boronic acids have also been developed. [16][17][18] A complementary and less widely exploited mode of reactivity for organoboron complexes of sugars is the activation of OH groups by formation of tetracoordinate adducts.…”
Section: Introductionmentioning
confidence: 99%
“…This observation appeared to be qualitatively consistent with our previous work, in which an electron-deficient boronic acid in combination with a trialkylamine provided optimal results for activation of a pyranoside towards reaction with a glycosyl halide donor. 24 Previous research from our lab had also identified 4-(trifluoromethyl)phenylboronic acid as a useful protective group for acylations, alkylations and glycosylations of carbohydrate derivatives, 14 indicating that a range of sequential transformations could potentially be achieved. It should be noted, however, that the data shown in Table 1 reflect an interplay between the reactivity of the Lewis base-boronic acid adduct and that of the Ag 2 Oactivated glycosyl bromide: a different result was obtained using an 'armed' glycosyl chloride (see below).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We surmised that since the C3 and C5 hydroxyls are in 1,3- syn relationship, they could be selectively masked to form a cyclic boronic acid ester, which, in theory, could be formed in situ and cleaved upon work up without introducing additional steps. While such strategy has been successfully implemented in carbohydrate synthesis, 18 we are unaware of its use for the single-pot selective glycosylation of 14-membered macrolactones or other non-carbohydrate-based natural products. Upon careful selection of the reaction conditions, the traceless in situ protection of 6-dEB with phenylboronic acid followed by glycosylation with A was accomplished to provide the corresponding C11 glycoside.…”
Section: Resultsmentioning
confidence: 99%
“…The only method we found to reliably functionalize this fickle diol was condensative borylation. 40 Heating oxane (±)-1a at 110 °C in the presence of boronic acids in toluene for 24 hours delivered the borylated species in generally good yields, Scheme 4. These borylated oxanes are hydrolytically unstable to silica, alumina, and water and thus could not be purified via extractive workup or chromatography.…”
mentioning
confidence: 99%